2021
DOI: 10.1108/ajems-04-2019-0155
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability responses to climate-smart adaptation in Africa: implication for food security among farm households in the Central Region of Ghana

Abstract: PurposeThe consequences of extreme climatic events that threaten food security have created the urgent need to properly adopt climate-smart adaptation techniques to improve productivity. The study examined the sustainability responses to climate-smart adaptation and the implication it has for explaining the food security situations among farm households in the Central Region of Ghana.Design/methodology/approachWe estimated Heckit treatment effect model to analyse cross-sectional data collected from randomly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…A large proportion of the African population relies on rain-fed farming for their livelihood (Adhikari et al, 2015 ; Cooper et al, 2008 ; Muchuru & Nhamo, 2019 ), so extreme climate variability poses a significant threat to food production (Boko et al, 2007 ; Etana et al ., 2021 ; Lobell et al, 2011 ; Schlenker & Lobell, 2010 ). Climate change and variability also raise food production costs, translating to high consumer prices (Berrera & Hertel, 2021 ; Dadzie et al, 2021 ; FAO, 2008 ). Evidence shows that climate change could decrease agricultural output in SSA by 8% by 2080, compared with a decrease of about 4% in Asia (Shah et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of the African population relies on rain-fed farming for their livelihood (Adhikari et al, 2015 ; Cooper et al, 2008 ; Muchuru & Nhamo, 2019 ), so extreme climate variability poses a significant threat to food production (Boko et al, 2007 ; Etana et al ., 2021 ; Lobell et al, 2011 ; Schlenker & Lobell, 2010 ). Climate change and variability also raise food production costs, translating to high consumer prices (Berrera & Hertel, 2021 ; Dadzie et al, 2021 ; FAO, 2008 ). Evidence shows that climate change could decrease agricultural output in SSA by 8% by 2080, compared with a decrease of about 4% in Asia (Shah et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was observed that forced relocation brought on by global warming results in individuals experiencing malnutrition or less availability of food. Dadzie et al (2021) evaluated the food safety circumstances of farmer families in Ghana's central zone to assess the durability of climate-savvy changes and their consequences. The cross-sectional data that were statistically obtained from a selection of farmers in the central area were analyzed using the approximated Heckit treatment effect theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, it is expected that low-latitude countries will experience adverse and consistent effects on crop production in the near future, especially for crops such as maize, wheat, and rice [6]. In this context, climate-smart agriculture (CSA) emerged as an approach to transform agricultural systems with the aim of supporting sustainable food production, food security, and sustainable development [7,8]. Even when there is no universally accepted definition of sustainable Land 2022, 11, 1268 2 of 16 development or sustainability, there is a general agreement regarding the three pillars or dimensions of sustainability: economy (human welfare), ecology (environmental integrity), and society (human relationships, equity, and social justice) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Another study on the adoption of CSA approaches conducted in Somalia in 2019 revealed that women largely performed key crop production practices and, therefore, identified this group as key players in implementing CSA practices and adaptation actions [34]. Since access to climate services (climate information based on scientific data that is useful to assist decisionmakers) is a fundamental component of CSA approaches [35], and it is generally limited to rural women [8], it is another important factor that should be considered when designing CSA strategies.…”
Section: Introductionmentioning
confidence: 99%